2021
DOI: 10.1111/beer.12399
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and employee attitudes: The moderating role of employee age

Abstract: This study examines the role of corporate social responsibility (CSR) on employee engagement and job satisfaction. Using 322 responses from employees of selected companies in Ghana, and employing hierarchical regression analysis, the study examines the direct impact of economic, legal, ethical and discretionary CSR practices on employee satisfaction and engagement in organisations. The study further explores the moderating role of employee age on the relationship between CSR and employee engagement and satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…As employees are older and have richer experiences, older employees have a more serious and positive attitude towards the organization's social responsibility, and they are more willing to gain recognition from leaders through their hard work and positive attitude. In the research on employee social responsibility and age, Nyuur et al also believed that employee age was proportional to social responsibility [ 34 ]. A more specific analysis is carried out, and it is concluded that there is no specific correlation between employees' education and organizational identification.…”
Section: Discussionmentioning
confidence: 99%
“…As employees are older and have richer experiences, older employees have a more serious and positive attitude towards the organization's social responsibility, and they are more willing to gain recognition from leaders through their hard work and positive attitude. In the research on employee social responsibility and age, Nyuur et al also believed that employee age was proportional to social responsibility [ 34 ]. A more specific analysis is carried out, and it is concluded that there is no specific correlation between employees' education and organizational identification.…”
Section: Discussionmentioning
confidence: 99%
“…The survey was completed by 465 employees, yielding a response rate of 32.29%. Considering the fact that not all the respondents must have been a part of EV, the response rate may be considered reasonable for the purpose of research (Nyuur et al , 2022). Of the 465 anonymous responses, a list-wise deletion of responses with missing values were removed and 444 were considered for data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…According to research, critical stakeholders seem to respond positively to CSR. For instance, evidence shows that CSR helps a firm increase customer satisfaction (e.g., Luo & Bhattacharya, 2006) and their willingness to pay a premium price (Bhattacharya & Sen, 2003; Ellen et al, 2000), increase employees' morale, job satisfaction, productivity, and identification with the company (Kim et al, 2010; Nyuur et al, 2022; Stuebs & Sun, 2010; Valentine & Fleischman, 2008), attract investors especially institutional investors (Barnett & Salomon, 2006; Johnson & Greening, 1999), and increase trust and commitment from suppliers (Su & He, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%